Eksistensi Pos Bantuan Hukum (Posbakum) Dalam Memberikan Pendampingan Hukum Kepada Masyarakat Di Pengadilan Agama Lubuk Pakam - Nia; Muhammad Saleh; Alang Sidek (Journal Smart Law, 2025)
This study examines the existence of the Legal Aid Post (Posbakum) at the Lubuk Pakam Religious Court in providing legal assistance to the underprivileged. As an effort to address this issue, the state has enacted regulations guaranteeing legal assistance, including Law Number 16 of 2011 concerning Legal Aid and Supreme Court Regulation Number 1 of 2014 concerning Legal Services for the Underprivileged. The background of the study is based on the public's low understanding of legalprocedures and limited access to legal services. The purpose of the study is to analyze the Posbakum service mechanism, the perceptions of service recipients, and supporting and inhibiting factors in its implementation. The method used is qualitative research with a descriptive approach. Data were obtained through observation, interviews with service recipients and Posbakum officers, and documentation from the Religious Court. Analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that Posbakum plays an important role in preparing lawsuits, legal consultations, and providing legal information. The community considers the existence of Posbakum very helpful, despite obstacles such as lack of socialization, limited facilities, and minimal legal understanding. The main supporting factors are the existence of regulations, state budget, and cooperation with legal aid institutions